Tax fairness and the tax mix - Duff, D (Foundation for Law, Justice and Society, 2008)
This brief considers the concept of tax justice or fairness in relation to each of these broad goals: the collection of revenues to finance public expenditures, the regulation of social and economic behaviour, and the distribution of economic resources. With respect to the collection of revenue for public expenditures, it argues that traditional principles of taxation according to benefits received and ability to pay provide useful criteria to assess the justice or fairness of taxes for this purpose. Regarding the regulation of social and economic behaviour, principles of tax fairness necessarily assume a different character, related to the justice of the regulatory goal, the presence of a rational relationship between the tax or tax incentive and the regulatory goal, and the distributional effects produced by the tax or incentive. Finally, it contends, where a tax is designed to affect the distribution of economic resources, principles of tax fairness dissolve into broader considerations of distributive justice which determine the manner in which economic resources are fairly distributed and the respective roles of taxes and transfer payments to achieve this distributive goal. Together, the brief concludes, these principles support a mix of taxes, including benefit taxes and user fees, a broad-based consumption tax like a value-added tax, excise taxes on specific goods and services, as well as progressive income and wealth transfer taxes.